Intensive Commercialization of Endangered Sharks and Rays (Elasmobranchii) Along the Coastal Amazon as Revealed by DNA Barcode - Martins, Thais; Santana, Paula; Lutz, Ítalo; da Silva, Raimundo; Guimarães-Costa, Aurycéia; Vallinoto, Marcelo; Sampaio, Iracilda; Evangelista-Gomes, Grazielle (Frontiers in Marine Science, 2021)
Elasmobranchs represent a well-defined group, composed of about 1,150 species inhabiting diverse aquatic environments. Currently, several of these species have been classified as threaten due to overexploitation. Therefore, we used DNA barcode to identify traded species of sharks and stingrays in the municipality of Bragança (Amazon coastal region), a major fishery landing site in northern Brazil. We collected a total of 127 samples labeled into 24 commercial nomenclatures over 1-year period. Twenty species were discriminated and 13 of them are recognized under some threatening status. In relation to sharks, Carcharhinidae showed the highest number of species, half of them classified as endangered, followed by hammerhead sharks (Sphyrnidae), with four species also regarded as threatened with extinction. The Rhinopteridae and Dasyatidae rays were the most abundant groups, with trade records of the following threatened species: Rhinoptera brasiliensis, Rhinoptera bonasus, Hypanus berthalutzae and Fontitrygon geijskesi. It is noteworthy that threatened species of elasmobranchs have been frequently and regularly exploited because of inefficient fishery management policies. Therefore, effective inspection practices need to be incorporated in fisheries, including the use of DNA barcode to enable a reliable method of species authentication and to assure the proper commercialization.